Studi Literatur Pengembangan Ilmu Pengetahuan Berkelanjutan Untuk Menyiapkan Generasi Indonesia Emas 2045 dalam Perspektif Filsafat Pendidikan - Nanang, Nanang; Mulyanti, Dety (LPPPI Publishing, 2025)
This research examines the development of sustainable knowledge within the perspective of educational philosophy to support the vision of Indonesia Emas 2045. Through a literature review method, this research highlights the importance of education as a fundamental basis for shaping a superior, innovative, and globally competitive generation. The integration of educational philosophy values into the curriculum is key to creating young generations capable of addressing the challenges of the Industrial Revolution 4.0 and 5.0, leveraging technology for innovation, and contributing to sustainable development. The results of this research provide insights for policymakers and educators in designing adaptive and future-oriented educational systems. With an education approach based on sustainable knowledge, Indonesia can prepare creative, critical, and solution-oriented human resources to support the achievement of national development targets towards Indonesia Emas 2045.